Konstruksi Kepemimpinan Transformatif di Lembaga Pendidikan Islam - Mahfudh Mahfudh (Indonesian Journal of Humanities and Social Sciences, 2022)
This article aims to describe the concept of transformative ideal leadership in Islamic education institutions. The approach used in this article is descriptive qualitative with the category of literature review, where this approach has the characteristics of collecting information and data using various types of available materials such as documents, books, magazines, and historical stories. This study found that the ideal of perspective leadership in Islam is that which has similarities with prophetic leadership. The ideal Transformational Leadership in Islamic educational institutions, must have 4 leadership traits in the Prophets and Apostles (prophetic). The four dimensions include Shiddiq (honest and true), Amanah (responsible, trustworthy), Tabligh (delivering messages, vision-mission), Fathanah (intelligent).